Economic analysis of traditional coconut oil production in Aceh Besar, Indonesia - *, Rahmattullah; ., Muhammad; Ismail, Muhammad Nasir (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to analyse the rentability and profit of traditional coconut oil production.Primary data was obtained by using survey method. Data collection techniques are conducted by census.The processing of oil is done by 6 respondents fermentation and 6 respondents cooking coconut milk. Theresults show that coconut oil production cooking coconut milk is more advantageous in terms of rentabilityand profit. The recommendation given is that the rural mothers switch  from fermentation to cooking ofcoconut milk